Small RNA‐binding protein RapZ mediates cell envelope precursor sensing and signaling in Escherichia coli. (17th February 2020) - Khan, Muna A; Durica‐Mitic, Svetlana; Göpel, Yvonne; Heermann, Ralf; Görke, Boris
Abstract: The RNA‐binding protein RapZ cooperates with small RNAs (sRNAs) GlmY and GlmZ to regulate the glmS mRNA in Escherichia coli . Enzyme GlmS synthesizes glucosamine‐6‐phosphate (GlcN6P), initiating cell envelope biosynthesis. GlmZ activates glmS expression by base‐pairing. When GlcN6P is ample, GlmZ is bound by RapZ and degraded through ribonuclease recruitment. Upon GlcN6P depletion, the decoy sRNA GlmY accumulates through a previously unknown mechanism and sequesters RapZ, suppressing GlmZ decay. This circuit ensures GlcN6P homeostasis and thereby envelope integrity. In this work, we identify RapZ as GlcN6P receptor. GlcN6P‐free RapZ stimulates phosphorylation of the two‐component system QseE/QseF by interaction, which in turn activates glmY expression. Elevated GlmY levels sequester RapZ into stable complexes, which prevents GlmZ decay, promoting glmS expression. Binding of GlmY also prevents RapZ from activating QseE/QseF, generating a negative feedback loop limiting the response. When GlcN6P is replenished, GlmY is released from RapZ and rapidly degraded. We reveal a multifunctional sRNA‐binding protein that dynamically engages into higher‐order complexes for metabolite signaling. Synopsis: Glucosamine‐6‐phosphate synthase GlmS produces precursor molecules for bacterial cell envelope synthesis. Here, protein RapZ in E. coli is shown to sense glucosamine‐6‐phosphate to regulate GlmS levels through interaction with the two‐component system QseE/QseF and the small RNAs GlmY/GlmZ. RapZ binds glucosamine‐6‐phosphate via its C‐terminal domain. Upon glucosamine‐6‐phosphate depletion, RapZ binds and activates the two‐component system QseE/QseF to induce transcription of the decoy sRNA GlmY. GlmY sequesters RapZ into stable complexes and titrates it away from GlmZ, which can then activate glmS expression by base‐pairing. Interaction with GlmY interferes with the ability of RapZ to activate QseE/QseF, providing a negative feedback loop. Glucosamine‐6‐phosphate releases GlmY from RapZ to trigger GlmY degradation, thereby allowing RapZ to target GlmZ for decay by RNase E. Abstract : RapZ regulates levels of the bacterial cell envelope precursor biosynthesis enzyme GlmS via interactions with glucosamine‐6‐phosphate, the two‐component system QseE/QseF and small RNAs GlmY/GlmZ.